2015
DOI: 10.3310/hta19860
|View full text |Cite
|
Sign up to set email alerts
|

Educational interventions to improve quality of life in people with chronic inflammatory skin diseases: systematic reviews of clinical effectiveness and cost-effectiveness

Abstract: The National Institute for Health Research Health Technology Assessment programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 100 publications
(470 reference statements)
0
43
0
2
Order By: Relevance
“…Our review complements and extends a number of related reviews that have recently been published, which examine the effect of psychological and educational interventions for eczema on treatment adherence, disease severity and quality of life . Our broader remit (all interventions designed to promote self‐management), strong critique of the methods and reporting, and the inclusion of recently published trials will help clinicians, researchers and commissioners better understand what we know about interventions that might help patients with eczema.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our review complements and extends a number of related reviews that have recently been published, which examine the effect of psychological and educational interventions for eczema on treatment adherence, disease severity and quality of life . Our broader remit (all interventions designed to promote self‐management), strong critique of the methods and reporting, and the inclusion of recently published trials will help clinicians, researchers and commissioners better understand what we know about interventions that might help patients with eczema.…”
Section: Discussionmentioning
confidence: 80%
“…Our review complements and extends a number of related reviews that have recently been published, which examine the effect of psychological and educational interventions for eczema on treatment adherence, disease severity and quality of life. [43][44][45] Our broader remit (all interventions designed to promote self-management), strong critique of the methods and reporting, and the inclusion of recently published trials will help clinicians, researchers and commissioners better understand what we know about interventions that might help patients with eczema. However, unfortunately, we are in agreement that there is still uncertainty about whether educational interventions are effective in improving quality of life for people with eczema; 46 most studies of parental education for eczema have been small and of poor quality; 44 and it is unknown which particular components are clinically effective and cost-effective in different clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…The methods for the systematic review were specified in a peer‐reviewed protocol, published on the NIHR website (http://www.nets.nihr.ac.uk/projects/hta/131101) and registered with PROSPERO (http://www.crd.york.ac.uk) (reference number: CRD4201400742) . The protocol development and review were informed by a project advisory group of practitioners, researchers and patient representatives, all of whom had experience or understanding of education programmes or chronic inflammatory skin conditions, including individuals who had designed or delivered these programmes.…”
Section: Methodsmentioning
confidence: 99%
“…To address these limitations, we conducted a systematic review of the effectiveness of educational interventions that aim to or could improve HRQoL in people with chronic inflammatory skin conditions and/or their carers. This research was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and reported in full in Pickett et al . Our review additionally focuses on a subset of education studies that included content beyond simply providing patients with information about the medical management of their condition.…”
mentioning
confidence: 99%
“…Могућност побољшања квалитета живота се разликује од пацијента до пацијента. Ве-лики позитиван утицајимајуповерење које је пацијент има у лекара, однос са партнером, активности у циљу побољшања социјалних и друштвених односа иразличити типови еду-кације како пацијената, тако и лекара у сми-слу пружања психолошке помоћи кроз одго-варајући приступ и разговор [6][7][8][9][10] . До сада је спроведен већи број студија које се баве факторима повезаним са смање-њем квалитета живота код псоријазе.…”
unclassified